2013
DOI: 10.1667/rr3054.1
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Risks from Plutonium: An Updated Analysis of Data from the Mayak Worker Cohort

Abstract: Workers at the Mayak nuclear facility in the Russian Federation offer a unique opportunity to evaluate health risks from exposure to inhaled plutonium. Risks of mortality from lung cancer, the most serious carcinogenic effect of plutonium, were evaluated in 14,621 Mayak workers who were hired in the period from 1948–1982, followed for at least 5 years, and either monitored for plutonium or never worked with plutonium. Over the follow-up period from 1953–2008, there were 486 deaths from lung cancer, 446 of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(124 citation statements)
references
References 18 publications
9
113
0
2
Order By: Relevance
“…To allow for a latent period in a radiation effect, analyses were also performed using the cumulative external dose and internal liver dose lagged by 0, 5, 10, 15 and 20 years. Because of indications that some workers were monitored for plutonium as a result of suspected diseases, person-years were classified as unmonitored until 2 years following the first monitoring date (Sokolnikov et al , 2008; Gilbert et al , 2013). The data were fitted to the following model:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To allow for a latent period in a radiation effect, analyses were also performed using the cumulative external dose and internal liver dose lagged by 0, 5, 10, 15 and 20 years. Because of indications that some workers were monitored for plutonium as a result of suspected diseases, person-years were classified as unmonitored until 2 years following the first monitoring date (Sokolnikov et al , 2008; Gilbert et al , 2013). The data were fitted to the following model:…”
Section: Methodsmentioning
confidence: 99%
“…The results from all of these models showed that attained age, gender and smoking status were the most important factors in modelling the background rates for other solid cancer incidence. However, the parametric approach produced a slightly better description of the background rates compared with the non-parametric approach, and this approach has also been used in previous analyses of Mayak cohort studies (Skolnikov et al , 2008; Gilbert et al , 2013). The final model for the baseline risks included a function of the gender-specific logarithm of attained age, the logarithm of attained age squared and gender-specific smoking status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our meta-analysis of the 27 independent observational studies provided strong evidence that LDIR increases solid cancer mortality risk, compared with control populations, despite the SMR being <1. Unfortunately, the large international cohort studies assessed the excess mortality risk of cancer using excess relative risk (ERR) rather than SMR (15,(31)(32)(33). We found that the high heterogeneity (I 2 =94.6%, P=0.00) in solid cancer mortality risk was attributed to the 6 complete studies, but there was enough evidence to conclude that LDIR could significantly increase brain and CNS cancer mortality risk (combined SMR=1.16; 95% CI: 1.02-1.31), regardless of whether the fixed-effects or random-effects model was used.…”
Section: Follow-up --------------------------------------------------mentioning
confidence: 99%
“…The Mayak worker cohort includes 25,757 workers hired during the period from 1948–1982 in one of the main plants (nuclear reactors, radiochemical plant, plutonium production facility) or in auxiliary plants involved with water treatment or mechanical repair (Gilbert et al 2013). Nearly all workers have dosimeter records of external exposure; workers in the radiochemical and plutonium production facilities had potential for plutonium exposure, which is mainly derived from bioassay measurements.…”
Section: Description Of the Components Of The Million Worker Studymentioning
confidence: 99%